2016
DOI: 10.1007/s00405-016-4163-6
|View full text |Cite
|
Sign up to set email alerts
|

Voice outcomes after thyroidectomy without superior and recurrent laryngeal nerve injury: VoiSS questionnaire and GRBAS tool assessment

Abstract: Voice symptoms are frequently reported early after thyroidectomy, even in the absence of laryngeal nerves injury. We evaluated the short-term outcomes of these functional alterations. Thirty-nine patients were enrolled in a prospective observational trial, evaluating voice function before and 3 months after uncomplicated thyroidectomy, using VoiSS as assessed using a validated patient rated questionnaire; and perceptual voice analysis using GRBAS scale (Grade, Roughness, Breathiness, Asthenia, Strain). Impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 15 publications
1
38
0
1
Order By: Relevance
“…It is suggested that patients should be advised of the possibility of vocal changes prior to surgery, regardless of the occurrence of laryngeal nerve damage during thyroidectomy, a suggestion also made by Tedla et al (2016) [33]. In addition to the guidelines on vocal aspects, the present study also reveals the importance of orienting patients regarding swallowing aspects, as several studies, including the present study, indicate that there is a possibility of dysphagia in this population [6,28,29,31,38,39].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is suggested that patients should be advised of the possibility of vocal changes prior to surgery, regardless of the occurrence of laryngeal nerve damage during thyroidectomy, a suggestion also made by Tedla et al (2016) [33]. In addition to the guidelines on vocal aspects, the present study also reveals the importance of orienting patients regarding swallowing aspects, as several studies, including the present study, indicate that there is a possibility of dysphagia in this population [6,28,29,31,38,39].…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, there is significant variability in the methods employed, especially with regard to the most adequate period for performing the evaluations [8,13,27,28]. It is evident that, regardless of how long after surgery the postoperative evaluation occurs -2 h; 1 day; on the 7th, 12th, or 60th day; 1, 3, or 6 months; or 4 years [6,15,24,27,29,[30][31][32][33][34][35] -the presence of upper airway, vocal and/or swallowing sensory disorders is found, suggesting that this alteration is not directly related to the existence of complications due to intubation, although Peppard and Dickens (1983) [36] and Pereira et al (2003) [24] reported that swallowing function can be altered due to the modification of the sensitivity of the intraoral, pharyngeal, and laryngeal region resulting from intubation.…”
Section: Discussionmentioning
confidence: 99%
“…The aerodigestive disorders associated with uncomplicated thyroidectomy are reported in several studies (2,(12)(13)(14). As commonly observed, they can also precede the surgery, and, in some cases, they can be explained as a consequence of the thyroid disease (3).…”
Section: Discussionmentioning
confidence: 98%
“…Symptoms such as hoarseness, sensation of a "lump", a "tootightly buttoned shirt collar", a "foreign body", "beeing strangled", "obstacle during swallowing" or cough are frequently described after thyroidectomy, even in absence of evident laryngeal nerve damage (12)(13)(14)(15). Several causes have been assumed to explain the association between thyroidectomy and voice and swallowing disorders.…”
mentioning
confidence: 99%
“…The VoiSS is 30-item questionnaire that yields a score from 1 to 120, where, conversely, a higher score reflects a more dysphonic voice and a poorer voice-related quality of life (Deary, Wilson, Carding, & MacKenzie, 2003). Both assessment tools have been widely used within the general voice literature (including non-organic voice impairment) however have not been used extensively within the laryngeal cancer literature specifically (Greulich, Parker, Lee, Merati, & Misono, 2015;Nixon, Ramsay, & Mackenzie, 2010;Paleri, Carding, Drinnan, Kelly, & Welch, 2010;Tedla, Chakrabarti, Suchankova, & Weickert, 2016;.…”
Section: Perceptual Assessments Of Voice and Communicationmentioning
confidence: 99%